Acceptance Rate of Family Planning Media Messages Among Residents of Obio/Akpor, Rivers State, Nigeria - Rhoda Iyane Idawari (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Media messages are essential for promoting family planning, but their acceptance and impact on behaviour vary across populations. This study assessed the acceptance rate of family planning media messages and associated factors among residents of Obio/Akpor Local Government Area, Rivers State, Nigeria. Methods: A community-based cross-sectional study was conducted among 310 residents of reproductive age (16–49 years) selected through multistage random sampling. Data were collected using a structured, self-administered questionnaire. Acceptance was measured through reported actions taken after message exposure, attitudinal change, and openness to receiving more information. Chi-square tests and binary logistic regression were performed. Statistical significance was set at p < 0.05. Results: The response rate was 95.1%. Mean age was 31.8 years (SD = 7.2), with 67.1% females and 32.9% males. Most respondents (71.9%) took action after exposure to family planning messages, 75.2% reported positive attitudinal change, and 86.8% were open to receiving more information. However, 81.0% agreed that myths and misinformation affect acceptance, and 87.1% emphasized the need for culturally tailored messages. Trust in official sources was high (83.2%). Educational level (p = 0.003), perceived message commonality (p < 0.001), trust in official sources (p < 0.001), and positive attitudinal change (p < 0.001) were significantly associated with high acceptance. Independent predictors of high acceptance were perceived message commonality (AOR = 4.06; 95% CI: 2.09–7.88), trust in official sources (AOR = 3.74; 95% CI: 1.96–7.14), positive attitudinal change (AOR = 4.39; 95% CI: 2.21–8.72), and post-secondary education (AOR = 2.23; 95% CI: 1.26–3.94). Conclusion: Acceptance of family planning media messages was moderately high in Obio/Akpor, but myths and misinformation remain barriers. Perceived message commonality, trust in official sources, attitudinal change, and education predicted acceptance. Culturally tailored, credible messages are needed to enhance family planning communication.